Manhaj Ibn Hibban dalam Kitab al-Ṡiqāt (Kritik Rijāl al-Ḥadīṡ Kategori Majhūl) - Arfan Arfan; Abustani Ilyas; Muhammad Sabir Maidin; La Ode Ismail Ahmad (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2022)
This study examined Ibn Hibban's manhaj in his work al-Ṡiqāt, with a particular emphasis on his criticism of rijāl al-hadīs majhūl category. This research utilized a historical and philosophical method, using data sources including Ibn Hibban's work al-Ṡiqāt, as well as additional books, books, and articles that explore al-jarḥ wa al-ta'dīl. The data were gathered from representative references, identified, selected, and cited based on their relevance to the issue, and then examined utilizing content analysis and comparison approaches. The findings of this analysis suggested that Ibn Hibban considered 'adālah to be the fundamental nature of a Muslim, such that if a narrator was not jarhed, 'adālah was what applied to him. Parts scholars believed that some of Ibn Hibban's evaluations in al-Ṡiqāt were accurate, while others believed they were not. This was because Ibn Hibban's rules contradicted the jumhur in determining the justice of a narrator, and there was a contradiction between Ibn Hibban's statement in al-Ṡiqāt and his practice, in which Ibn Hibban included narrators who he himself determined were not ṡiqah under various categories and for a specific purpose. In contrast to Ibn Hibban's manhaj, Ibn Hibban included the narrators of the majhūl in al-Ṡiqāt since they were not plundered.